2014
DOI: 10.1007/s12032-014-0084-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between infection of hepatitis B virus and onset risk of B-cell non-Hodgkin’s lymphoma: a systematic review and a meta-analysis

Abstract: Whether an association between hepatitis B virus (HBV) infection and B-cell non-Hodgkin's lymphoma (B-NHL) risk exists is an open question. In order to provide quantification of the issue, we carried out a meta-analysis of the published data. We identified 4 case-control and 2 nested case-control studies, including a total of 5,396 B-NHL cases. We derived meta-analytic estimates using random-effects models, taking into account the correlation between estimates. The odds radio (OR) of HBV infection in B-NHL whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Although considerable evidence has accumulated on the association between HBV infection and NHL, to date, only a few reviews have evaluated the summary risk of NHL among HBV infection patients . The most recent review was in 2015 .…”
Section: Discussionmentioning
confidence: 99%
“…Although considerable evidence has accumulated on the association between HBV infection and NHL, to date, only a few reviews have evaluated the summary risk of NHL among HBV infection patients . The most recent review was in 2015 .…”
Section: Discussionmentioning
confidence: 99%
“…Some, but not all, epidemiological studies have reported an association between HBV infection and hematological malignancies, mostly NHLs. Meta‐analyses of these observational studies found a significant association with a pooled odds ratio of greater than 2 for NHL . HBV can infect lymphocytes and as for the well‐known association between HCV infection and NHL, investigators have hypothesized that chronic B‐cell antigenic stimulation may play a role in lymphomagenesis in people chronically infected with HBV .…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of these observational studies found a significant association with a pooled odds ratio of greater than 2 for NHL. 35 HBV can infect lymphocytes and as for the well-known association between HCV infection and NHL, investigators have hypothesized that chronic B-cell antigenic stimulation may play a role in lymphomagenesis in people chronically infected with HBV. 36 In our study, we had sufficient power to evaluate specific subtypes of NHL.…”
Section: Discussionmentioning
confidence: 99%
“…A direct demonstration that HBV is involved in the development of NHL will offer a positive answer. In addition, if HBV contributes to lymphomagenesis, HBV vaccination will reduce the incidence of NHL, even though this impact may only be observed following a long time interval (3,(6)(7)(8). A number of case-control studies concerning HBV with large cohorts have been published (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%